(untitled) (Vietnam Journal of Community Medicine, 2026)
Renal biopsy is the gold standard in the diagnosis of glomerular diseases, helping to guide and individualize treatment, especially treatment with immunosuppressive drugs. Objective: To evaluate the rate and characteristics of changes in indications for immunosuppressive drug treatment after renal biopsy results in patients with glomerular diseases. Methods: Observational cohort. Location: Center for Nephrology, Urology and Dialysis, Bach Mai Hospital. Time: From January 2024 to February 2026. Results: A total of 554 patients were studied. The rate of patients whose immunosuppressive drug treatment was changed after renal biopsy results was 46%, and there were differences among groups of glomerular diseases. The rate of change was 100% in rapidly progressive glomerulonephritis, 74.5% in lupus nephritis, 44.7% in IgA nephropathy, 37.3% in nephrotic syndrome, and 35.1% in other glomerular diseases. Among the patients whose treatment was changed, 31.8% were started on immunosuppressive drugs, 56.9% had their immunosuppressive drug treatment intensified, 3.1% had the treatment intensity reduced, 5.1% were switched to another regimen, and 3.1% discontinued immunosuppressive drugs. Conclusion: The rate of patients whose immunosuppressive drug treatment was changed after renal biopsy results was 46%, of whom the majority were started on or had their immunosuppressive drug treatment intensified.